2022
DOI: 10.1016/j.jaad.2021.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision margins for fibrohistiocytic tumors, including atypical fibroxanthoma and undifferentiated pleomorphic sarcoma: A probability model based on a systematic review

Abstract: Background: Mohs micrographic surgery or wide local excision is the treatment of choice for fibrohistiocytic tumors with metastatic potential, including atypical fibroxanthoma (AFX) and cutaneous undifferentiated pleomorphic sarcoma (cUPS). Since margin clearance is the strongest predictor of clinical recurrence, improved recommendations for appropriate surgical margins help delineate uniform excision margins when intraoperative margin assessment is not available.Objective: To determine appropriate surgical wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…However, to date, no guidelines for surgical treatment and follow-up have been established [ 23 ]. A recently published probability model based on a systemic review by Jibbe et al found peripheral excision margins of at least 2 cm for AFX and 3 cm for PDS, respectively, to reduce the recurrence rate [ 26 ]. However, the current standard of care in the treatment of AFX is due to its intermediate malignant potential, micrographically controlled excision with a narrow clearance margin appears to be sufficient [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, no guidelines for surgical treatment and follow-up have been established [ 23 ]. A recently published probability model based on a systemic review by Jibbe et al found peripheral excision margins of at least 2 cm for AFX and 3 cm for PDS, respectively, to reduce the recurrence rate [ 26 ]. However, the current standard of care in the treatment of AFX is due to its intermediate malignant potential, micrographically controlled excision with a narrow clearance margin appears to be sufficient [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current standard of care in the treatment of AFX is due to its intermediate malignant potential, micrographically controlled excision with a narrow clearance margin appears to be sufficient [ 11 ]. In any case, margin-controlled surgery is favorable for ensuring complete removal and reducing resection morbidity [ 26 ]. Although the number of cases is limited, we found no local recurrence of atypical fibroxanthoma when margin-controlled surgery was performed with a margin clearance of 1.50 cm at the median (IQR 1.4–2).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on what is an adequate margin distance for minimizing the risk of local recurrence. When UPS occurs in the extremities, the resection margin should be at least 1–3 cm away from the gross border ( 33 , 34 ). However, if UPS is located in the retroperitoneum, complete compartmental resection will produce significantly better results ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…No guidelines on surgical management and follow-up exist. In a recent study reviewing 100 published cases suggesting a probabilistic model, the appropriate surgical margins were found to be at least 2 cm for AFX and at least 3 cm for DUPS to clear 95% of all tumours [ 61 ]. Electrochemotherapy is a very recent potential treatment method for recurrent DUPS [ 62 ].…”
Section: Treatment Algorithms and Strategiesmentioning
confidence: 99%